The impact of co-morbidity on health-related quality of life in breast cancer survivors and controls. (May 2015) - Schoormans, Dounya; Czene, Kamila; Hall, Per; Brandberg, Yvonne
Abstract Background. The objective of this study was: 1) to compare health-related quality of life (HRQoL) scores of breast cancer survivors to matched controls; and 2) to examine the relative impact (explained variance) of the type and number of co-morbidities on HRQoL. Material and methods. Data from the KARMA project was used in this cross-sectional study. For each woman diagnosed with breast cancer (n = 2552) there were two healthy age- and geographically matched females (n = 5104). Breast cancer survivors were categorized according to time since diagnosis: recently diagnosed (0–1 year), short- (2–5 years), mid- (6–10 years), and long-term survivors (> 10 years). Women completed a questionnaire addressing demographics (age, educational level, and geographical location), lifestyle factors (body mass index (BMI) and smoking), co-morbidities, and HRQoL. The difference in explained variance in six HRQoL-domains between demographics, lifestyle factors, and co-morbidity in women with breast cancer and matched controls was examined by hierarchical regression analyses. Results and conclusion. Women recently diagnosed (n = 63), reported the worst HRQoL followed by short-term survivors (2–5 years, n = 863). Thereafter, HRQoL scores further improved (6–10 years, n = 726), and were comparable to healthy females after 10 years (n = 893). Co-morbidity has a negative impact on HRQoL, which increased with time after diagnosis. Cardiovascular disease and depression were the strongest associates. Breast cancer survivors report clinically significant improvement in HRQoL scores six years after diagnosis. Co-morbidity has a negative impact on HRQoL, which increases with time after diagnosis, even though the number of co-morbidities remains stable. In long-term survivors there should be increasing awareness of co-morbidity and its impact on HRQoL.